Production of Styrene from Dehydrogenation of Ethylbenzene. Issue 5 (5th April 2022) - Gupta, Rahul; Uslu, Hasan; Majumder, Subhajit
Abstract: A pseudo‐homogeneous model based on intrinsic rate equations for dehydrogenation of ethylbenzene to styrene in an adiabatic fixed‐bed reactor is developed. Steam and ethylbenzene are the main reactants with styrene as the desired product, and benzene and toluene as by‐products. Styrene production is an endothermic reaction depends on various factors such as temperature, pressure, steam to ethylbenzene ratio, styrene to ethylbenzene ratio in feed. These factors affects the properties like styrene selectivity, ethylbenzene and by‐product conversion etc. The development of the mathematic model includes the application of mass balance, energy balance, and basic thermodynamic relations, momentum balance, Langmuir and Hinshelwood model, Ergun relation, etc. The effects of temperature as well as of the steam‐to‐ethylbenzene and styrene‐to‐ethylbenzene molar ratios in the feed on the selectivity for styrene, ethylbenzene conversion, and conversion to by‐products are also evaluated. The maximum selectivity for styrene can be achieved at increased steam‐to‐ethylbenzene feed ratio and a lower ethylbenzene conversion. Abstract : For dehydrogenation of ethylbenzene into styrene in an adiabatic fixed‐bed reactor, a pseudo‐homogeneous model based on intrinsic rate equations is developed based on application of different relations, Langmuir and Hinshelwood model, Ergun relation, etc. The impact of these key factors on styrene conversion and selectivity using MATLAB software with the required model equations and coding is described.